Role of depression and its associating factors in indoor orthopaedic patients - Jain, Ravikant; Rishi, Rahul; Sharma, Balkishan; Kiyawat, Vivek (Asian Journal of Medical Sciences, 2015)
Background and Objectives: Depression has acknowledged and well documented, is common among orthopaedic inpatients may be associated with functional outcomes. Authors aimed to investigate the role, prevalence and associating factors of depression disorder in orthopaedic inpatients. Materials and Methods: A cross-sectional study is designed among patients that admitted at SAIMS, Indore. Four hundred twenty six orthopedic patients were recruited for study. The demographic and clinical measurements were recorded. Levels of depression were assessed by using Zung’s depression scale. Results: Depressive disorder was identified in 87.6% indoor patients significantly (p<0.001) influenced female more than male. The mean depression score in female (67.37±11.75) was significantly higher than male (62.29±12.20). The prevalence of extreme/major depression in female (46.6%) was higher as compared to male (25.7%). Type of trauma was found significantly (p<0.05) associated with depressive disorder. 38.1% male with traumatic condition and 20.0% with non-traumatic condition had moderate depression in comparison to 31.4% and 13.6% female. Depressive disorder was found significantly associated with sex (p<0.001), socio-economic status (p<0.001), length of ortho-illness (p<0.001), length of stay in hospital (p<0.001), exercise/yoga (p<0.05) and type of injury (p<0.05). Conclusions: Higher incidence of depressive disorder recorded in female. Prevention and treatment require more clinical and research attention to reduce the public health burden of depression. The study suggested that higher depressive disorder does occur in indoor orthopaedic patients that associated with various functional outcomes. This study supports the view of depressive disorder was disabling factor in better functional recovery and frequent in female after orthopedic trauma. DOI: http://dx.doi.org/10.3126/ajms.v6i6.12478 Asian Journal of Medical Sciences Vol.6(6) 2015 70-76